Diagnostic performance of endobronchial ultrasound‐guided mediastinal lymph node sampling in early stage non‐small cell lung cancer: A prospective study. Issue 1 (30th August 2017) - Vial, Macarena R.; O'Connell, Oisin J.; Grosu, Horiana B.; Hernandez, Mike; Noor, Laila; Casal, Roberto F.; Stewart, John; Sarkiss, Mona; Jimenez, Carlos A.; Rice, David; Mehran, Reza; Ost, David E.; et al.
ABSTRACT: Background and objective: Standard nodal staging of lung cancer consists of positron emission tomography/computed tomography (PET/CT), followed by endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) if PET/CT shows mediastinal lymphadenopathy. Sensitivity of EBUS‐TBNA in patients with N0/N1 disease by PET/CT is unclear and largely based on retrospective studies. We assessed the sensitivity of EBUS‐TBNA in this setting. Methods: We enrolled patients with proven or suspected lung cancer staged as N0/N1 by PET/CT and without metastatic disease (M0), who underwent staging EBUS‐TBNA. Primary outcome was sensitivity of EBUS‐TBNA compared with a composite reference standard of surgical stage or EBUS‐TBNA stage if EBUS demonstrated N2/N3 disease. Results: Seventy‐five patients were included in the analysis. Mean tumour size was 3.52 cm (±1.63). Fifteen of 75 patients (20%) had N2 disease. EBUS‐TBNA identified six while nine were only identified at surgery. Sensitivity of EBUS‐TBNA for N2 disease was 40% (95% CI: 16.3–67.7%). Conclusion: A significant proportion of patients with N0/N1 disease by PET/CT had N2 disease (20%) and EBUS‐TBNA identified a substantial fraction of these patients, thus improving diagnostic accuracy compared with PET/CT alone. Sensitivity of EBUS‐TBNA however appears lower compared with historical data from patients with larger volume mediastinal disease. Therefore, strategies to improve EBUS‐TBNA accuracy in this population should be further explored Abstract : See related Editorial We assessed the sensitivity of endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) in patients with lung cancer staged as N0/N1 by positron emission tomography/computed tomography (PET/CT). EBUS‐TBNA improved the pretreatment staging of these patients compared with PET/CT; however, the sensitivity for N2 disease is only 40%, lower than sensitivities previously reported for N2/N3 patients.